Industry innovation in the era of artificial intelligence : the AI compass - Wang, Xiaomei (CRC Press Women in AI Series, 2025)
This book explores the multifaceted nature of AI implementation in modern business strategy, focusing on its present and future impact on various sectors. The book will spark fresh thinking and provide a driving force for global industrial innovation. Author Xiaomei Wang, Founder and CEO of PathoAI, former Global Leader of Big Data and Analytics at IBM, as well as General Manager of IBM Growth Markets Unit Big Data Centers, draws on over 20 years of experience in data analytics and AI to offer unique insights and a rich collection of compelling industry case studies.Designed for business leaders, tech enthusiasts, and policymakers alike, this book is not just a manual for understanding AI, but a road map for harnessing its potential. By offering a blend of theoretical insight and practical guidance, this book empowers readers to embrace AI as a catalyst for innovation and sustainable growth in their respective fields